Análise do desempenho físico-mecânico de compósitos cimentício com adição de partículas de madeira eucalipto - Leite, Murilo Augusto Verissimo [UNESP]; Campos, Cristiane Inácio De [UNESP]; Souza, Alexandre Jorge Duarte De [UNESP]; Molina, Julio Cesar; Silva, Maria Fernanda Felippe [UNESP]; Silva, João Vítor Felippe (Associação Nacional de Tecnologia do Ambiente Construído - ANTAC, 2025)
The use of composite materials produced with the addition of renewable raw materials has gained broad acceptance due to the increasing scarcity of natural resources. This research aimed to analyze the performance of composites produced with cement and wood using two different binders, with a focus on evaluating compressive strength at 28 days and bulk density. A total of 48 cement-wood specimens were produced, distributed across 8 treatments, each with 6 specimens. These treatments varied in terms of the type of Portland cement used (CP2 and CP5), the condition of Eucalyptus grandis wood particles (pre-treated with cold water or untreated), and the use of calcium chloride additive. The mechanical compression test was performed to determine the secant modulus of elasticity (Ecs,28) and the average compressive strength of concrete at 28 days (fcm), as well as the apparent density of the composites. Treatments with Portland CP5 cement and additives showed better mechanical performance.

A utilização de materiais compósitos produzidos com adição de matérias-primas renováveis tem conquistado ampla aceitação devido à crescente escassez de recursos naturais. Esta pesquisa teve como objetivo analisar o desempenho de compósitos produzidos com cimento e madeira com dois diferentes aglomerantes, visando avaliar a resistência à compressão aos 28 dias e a densidade aparente. Foram produzidos um total de 48 corpos de prova de cimento-madeira, distribuídos em 8 tratamentos, cada um com 6 corpos de prova. Esses tratamentos variaram em relação ao tipo de cimento Portland utilizado (CP2 e CP5), à condição das partículas de madeira de Eucalyptus grandis (pré-tratadas com água fria ou in natura) e uso do aditivo cloreto de cálcio. Foram realizados o ensaio mecânico de compressão para a determinação do módulo de elasticidade secante (Ecs,28) e da resistência média do concreto à compressão aos 28 dias (fcm) e da densidade aparente dos compósitos. Os tratamentos com cimento Portland CP5 e com aditivos tiveram melhores desempenho mecânico.
Analysis of the physical-mechanical performance of cementitious composites with the addition of eucalyptus wood particles
Keywords: Wood-cement; Sustainability; Sustainability materials; Madeira-Cimento; Sustentabilidade; Materiais sustentáveis